The Entrepreneurs in Breed: The Case of Acehnese Dayah, Indonesian Traditional Islamic Boarding School - Malasyi, Sibral; Batubara, Maryam; Siregar, Saparuddin (Jurnal Minds: Manajemen Ide dan Inspirasi, 2024)
The combination of entrepreneurial spirit and religion has been widely discussed. However, the integrated school program combines lessons on business management, marketing, and entrepreneurial skills with religious studies. This article explores this topic in a natural setting, contributing to the academic discussion on how participants, equipped with both knowledge and practical skills, require sufficient program support to effectively start and manage businesses. The findings reveal the success in producing graduates who are well-rounded, with a solid foundation in both religious education and business. This integration prepares alumni to launch ventures with comprehensive expertise. Feedback from alumni indicates that the skills gained through these significant measures have played a crucial role in the successful planning and management of their businesses.